Interactive Multimedia Based on Android Applications: Development of Learning Media for Non-Formal Schools - Susanto, Susanto; Burmansah, Burmansah; Sutawan, Komang; Seneru, Wistina; Rapiadi, Rapiadi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Learning media encourages learning. Limitations of learning media in Buddhist education in Sunday schools give impetus to researchers to develop multimedia to develop appropriate media. This research aims to build Android application-based learning media on the material of puja facilities and infrastructure in Buddhism. A Multimedia set is expected to be able to provide good results in learning. This approach uses research and development methods to develop Android-based Multimedia as a learning medium for Buddhist Sunday Schools in Pesawaran Regency. The study population was 144, with a sample of 21 learners. The development flow refers to the Bord and Gall development steps. The data analysis technique used is descriptive percentages to determine the questionnaire's validity and reliability and evaluate the product's effectiveness—assessment of product trials tested to media experts, material experts, and teacher and student users. The results showed that Android-based Multimedia had passed validation and operational tests with reasonable criteria, and the effects of field tests showed a significant difference between the average scores before and after using the application. Therefore, the application developed can be an effective learning medium for Buddhist Sunday Schools.